“Media-Event” In The Information Service - Raykhona Tolbjon Kizi Ochilova; Yokutkhon Mamasobirovna Erkaboeva (International Scientific and Current Research Conferences, 2020)
Today, not only in Uzbekistan, but also in other developed countries, "one of the main priorities of the Information Service Officer is to establish good relations with the public." There is a lot of work to be done in this regard. There are new concepts, new terms, one of which is a media event that is just entering Uzbekistan. There are also goals and objectives of information services.